Hubungan Antara Menonton Acara Kekerasan Televisi Dengan Perilaku Agresif Siswa SMP di Salatiga - Pradana, Yosua Ivan; Dwikurnaningsih, Yari; Setyorini, Setyorini (Universitas Kristen Satya Wacana, 2018)
This study aims to determine the significance of the relationship between watching the violence shown on television with aggressive behavior of junior high school students in Salatiga. The hypothesis put forward is that there is a significant relationship between watching television violence shows with aggressive behavior of junior high school students in Salatiga. The study was conducted in one of the junior high schools in Salatiga. Sampling technique in this research using stratified random sampling technique. The questionnaire used was a questionnaire of aggressive behavior of teenagers and questionnaires watching the violence on television. The analytical method used is Kendalls tau correlation technique. Based on the data analysis obtained correlation value 0.811 with a significance level of 0.000 (p <0.05). These results indicate that there is a significant relationship between watching the violence shown on television and the aggressive behavior of junior high school students in Salatiga. The higher the students watch the violence on television, the higher the aggressive behavior. Thus the hypothesis proposed in this study is accepted.